Documentary film: the evolutions of Jejak Rasul by TV3 to attract young viewers in UiTM Rembau / Faezatul Adilah A Sabri - A Sabri, Faezatul Adilah (2018)
This study aims to see the impact of the documentary on influencing the behavior of the audience. The effectiveness of film filming on young audiences is to become a platform for education. This study uses quantitative methods. Respondents were randomly selected from 3 faculties in Uitm Rembau. This study is made possible to help bring back the documentary film that is fading. 'Jejak Rasul' is one of the documentary programs that are all-mentioned. The Jejak Rasul Series was first aired on TV3 during Ramadan in 1995. Jejak Rasul is a 30-episode documentary that depicts the struggle of the 25 prophets as mentioned in the Quran. The documentary takes the style of a travelogue that covers various locations in the history and lives of the prophets and the Rasuls. mThe main aim of this documentary was to educate the public on the way of life of the prophets and their struggles to uphold the teachings of the holy Quran.